Pengaruh Kualitas Pelayanan dan Persepsi Harga terhadap Kepuasan Pelanggan pada ID Express Surabaya - Walyullah, Muhammad Muizzu Adlu; Pudjoprastyono, Hery (Universitas Batanghari, 2024)
The aim of this study was to investigate the impact of service quality and price perceptions on customer satisfaction at ID Express Surabaya. The present investigation employed a sample size of 60 individuals who have utilized or are presently utilizing the ID Express shipping services. The present investigation collected data through the administration of questionnaires in the Surabaya region. The researcher employed independent variables, specifically Service Quality (X1) and Perceived Price (X2), as well as a dependent variable, namely Customer Satisfaction (Y). The present investigation employs an analytical framework in the form of Partial Least Square (PLS), a method utilized to develop a model that can be presumed in the presence of multiple factors. The findings of the present investigation suggest that the perception of service quality and price can exert a favorable influence on customer satisfaction levels at ID Express Surabaya.